2015
DOI: 10.1371/journal.pone.0123629
|View full text |Cite
|
Sign up to set email alerts
|

Millennium Development Goal Four and Child Health Inequities in Indonesia: A Systematic Review of the Literature

Abstract: IntroductionMillennium Development Goal (MDG) 4 calls for reducing mortality of children under-five years by two-thirds by 2015. Indonesia is on track to officially meet the MDG 4 targets by 2015 but progress has been far from universal. It has been argued that national level statistics, on which MDG 4 relies, obscure persistent health inequities within the country. Particularly inequities in child health are a major global public health challenge both for achieving MDG 4 in 2015 and beyond. This review aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…In particular, the differing patterns of quality scores seen between and within regions in Indonesia suggests that place of residence may have a greater influence on determining the quality of maternal and neonatal care than wealth or urban-rural status alone. This is perhaps unsurprising given the heavily decentralised nature of Indonesia’s health system; significant regional variation has been noted for other health related measures such as child mortality [ 36 , 37 ], and observational data suggest that the performance of local health systems varies substantially from district to district. Countries with more highly centralised health systems would be expected demonstrate different patterns of variation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the differing patterns of quality scores seen between and within regions in Indonesia suggests that place of residence may have a greater influence on determining the quality of maternal and neonatal care than wealth or urban-rural status alone. This is perhaps unsurprising given the heavily decentralised nature of Indonesia’s health system; significant regional variation has been noted for other health related measures such as child mortality [ 36 , 37 ], and observational data suggest that the performance of local health systems varies substantially from district to district. Countries with more highly centralised health systems would be expected demonstrate different patterns of variation.…”
Section: Discussionmentioning
confidence: 99%
“…External factors, such as household environment, also influences stunting (Aryastami & Tarigan, 2017). Living in a rural area increases the risk of malnutrition, and the number of stunted children, compared to living in metropolitan areas (Schröders, Wall, Kusnanto, & Ng, 2015). Children who live in metropolitan areas are less at risk than children who live in rural areas.…”
Section: Living Areamentioning
confidence: 99%
“…A systematic review of women's empowerment and child malnutrition status in South Asia [18] reported that women's low social status is generally associated with children's poor nutritional status; however, there is a great deal of disparity in the literature and a need for further studies. Moreover, a systematic review on child health inequalities in Indonesia found that the association between mothers' household decision-making and child health is rather unexplored [19]. Nevertheless, quantitative approaches to analysing data, which are generally the only available sources for population studies, would most often miss the relational and emergent mechanisms within households and between their individuals who encounter different forms of malnutrition; for instance, undernutrition among children and overnutrition among mothers.…”
Section: Introductionmentioning
confidence: 99%